Peningkatan Kinerja SDM UMKM Melalui Pelatihan Media Sosial Untuk Pemasaran Dan Branding - Praningrum, Praningrum; Puspita, Anggri; Daulay, M Yasser Iqbal; Nasution, Suswati (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The purpose of this PKM activity is to provide basic HRM training for Micro, Small and Medium Enterprises of Central Bengkulu. The method of community service activities begins with the preparation stage and problem identification through field surveys. The survey was conducted by looking at the condition of SMES and discussing directly with the Owner of Central Bengkulu SMES. The survey intends to identify the needs and opportunities for the need for social media for SMES business actors. Then, the socialization and training stages were carried out by the team. The result of this community service activity is the knowledge of participants, in this case SMES business actors, regarding the need for social media to increase marketing and product branding. After the PKM activities were carried out and the material presentation was delivered, it was found that the participants' knowledge about social media had increased.